Effects of magnetic fields on an unsteady mixed convective boundary layer flow of an electrically conducting fluid with temperature dependent properties - Kitengeso, Raymond; Mureithi, Eunice; James, Makungu; Mango, John (Tanzania Journal of Science, 2021)
A mixed convective boundary layer flow of an electrically conducting fluid with temperature dependent properties over an inclined plate is investigated. The magnetohydrodynamic boundary layer governing equations are derived by using Boussinesq and boundary layer approximations. The equations are transformed to similarity form using a similarity transformation variable and the resulting boundary value problem is solved numerically. The effects of magnetic fields, unsteadiness, mixed convection and variable fluid properties on velocity and temperature in the boundary layer are analysed. The effects of pertinent parameters on skin friction and heat transfer are also analysed